'A Doctrine Quite New and Altogether Untenable': Defending the Beneficiary Pays Principle. (25th July 2014) - Butt, Daniel
Abstract This article explores the ethical architecture of the 'beneficiary pays' principle, which holds that agents can come to possess remedial obligations of corrective justice to others through the involuntary receipt of benefits stemming from injustice. Advocates of the principle face challenges of both persuasion and limitation in seeking to convince those unmoved of its normative force, and to explain in which cases of benefiting from injustice it does and does not give rise to rectificatory obligations. The article considers ways in which advocates of the principle might seek to win over those sceptical of its merits by employing a modified principle which sidesteps the issue of enforceability, before considering the question of whether the argument can be expanded from cases of benefiting from wrongdoing specifically to other sorts of situation where one agent involuntarily benefits from another's loss.